Організаційно-економічний механізм відтворення ресурсного потенціалу суб’єктів аграрного бізнесу в умовах інклюзивної економіки - Степаненко, С. В. (Причорноморські економічні студії, 2022)
У статті запропоновано модель організаційно-економічного механізму відтворення ресурсного потенціалу суб’єктів аграрного бізнесу в умовах інклюзивної економіки, окреслено принципи його функціонування та функціональний спектр синергійної взаємодії його основних елементів. Встановлено, що інклюзивність організаційно-економічного механізму управління відтворенням ресурсного потенціалу агробізнесу ґрунтується на одновекторній взаємодії трьох базових стовпів сталого розвитку: агроекологічний ресурсний масштаб; соціальнотериторіальний ресурсний масштаб; економічно-ресурсний масштаб. Визначено перелік та обґрунтовано зміст принципів інклюзивного механізму управління відтворенням ресурсного потенціалу бізнес-суб’єктів аграрної сфери. Розкрито функціонал інклюзивного організаційно-економічного механізму. Обґрунтовано, що основними інструментами створення сприятливих інституційних умов для відтворення ресурсного потенціалу агробізнесу і сільських територій мають стати: суспільне мислення і сприйняття важливості і особливостей даного завдання, система мотиваторів і інтересів кожного учасника даного процесу, партнерство і відповідальність у всіх напрямах відтворення. The article proposes a model of the organizational and economic mechanism for reproducing the resource potential of agrarian business entities in the conditions of an inclusive economy, outlines the principles of its functioning and the functional spectrum of synergistic interaction of its main elements. It was established that the inclusiveness of the organizational and economic management mechanism for the reproduction of the resource potential of agribusiness is based on the one-vector interaction of three basic pillars of sustainable development: agro-ecological resource scale; socio-territorial resource scale; economic and resource scale. The goal of the participants of the inclusive organizational and economic management mechanism for the reproduction of the resource potential of business entities in the agrarian sphere is determined – sufficient quantity and quality of all types of resources for solving the strategic tasks of sustainable development of agribusiness and rural areas. The realization of this goal involves the adoption by all participants of the reproduction process of the basic principles of resource potential management: participation, justice, growth, equality of opportunities, sustainability, stability, long-term social orientation. The functionality of the inclusive organizational and economic mechanism is determined: preservation and reproduction of eco- and bioagrosystems; increasing the added value of agribusiness in value chains; increasing the level of efficiency and competitiveness of agrarian business; promoting the implementation of social, environmental and economic tasks of sustainability; activation of the country's participation in the global trends of socio-economic development; increasing the level of integration of the national agricultural sector into the global digital business plane; development of mechanisms of private-partnership relations as a promising direction of integration relations. It is substantiated that the main tools for creating favorable institutional conditions for the reproduction of the resource potential of agribusiness and rural areas should be: social thinking and perception of the importance and peculiarities of this task, a system of motivators and interests of each participant in this process, partnership and responsibility in all areas of reproduction.
Organizational and economic mechanism of reproducing the resource potential of agricultural business subjects in the conditions of an inclusive economy
Keywords: відтворення; ресурсний потенціал; інклюзивна економіка; організаційно-економічний механізм; суб’єкти аграрного бізнесу; інструментарій; reproduction; resource potential; inclusive economy; organizational and economic mechanism; subjects of agrarian business; tools